Manfaat ekstrak etanol daun inai (lawsonia innermis l.) Sebagai bahan pewarna alami untuk kontrol plak (kajian pada tikus sprague dawley) - Lies Zubardiah; Zahra Salsabil Putri Rivai (Fakultas Kedokteran Gigi Universitas Trisakti, 2023)
Plaque is a soft, colorless deposit containing bacteria that adheres to the surface of the teeth and surrounds the gingiva and other hard surfaces in the oral cavity. A disclosing agent is a selective dye that can detect the presence of dental plaque by changing the color of the plaque so that it contrasts with the tooth surface. Henna has many properties and can produce staining. Lawsone is the main ingredient in the henna plant. Lawsone has a high affinity for binding to proteins and causing staining. The aim is to determine the potential of henna leaf extract (L. inermis L.) as a natural disclosing agent. Laboratories carried out experimental research using rats as experimental animals. The rats were divided into seven groups: control, henna leaf ethanol extract (100%), 50% (25%) group, 12.5% (6.25%), and 3.125% (3.5%) group. The henna leaf ethanol extract group with a concentration of 50% that was left for 30 seconds produced a color close to the positive control used, namely the disclosing agent. The ethanol extract of henna leaves with a concentration of 50%, which was left for 30 seconds, produced a brown to grayish brown color on rat dental plaque and has the potential to be a natural disclosing agent.